The development and validation of an analytical method for doxycycline quantification in human plasma - doi:10.5020/18061230.2007.p193 - Geysa Aguiar; Eunice Kazue Kano; Clarice Madalena Bueno Rolim; Cristina Helena dos Reis Serra; Humberto Gomes Ferraz; Valentina Porta (Universidade de Fortaleza, 2012)
The aim of this study was to develop and validate a simple, quick and sensitive assay for determination of doxycycline concentration in human plasma by High Performance Liquid Chromatography (HPLC). Doxycycline and Oxytetracycline (internal standard) were extracted from 0,5 mL human plasma into ethyl acetate. The HPLC system was operated isocratically at controlled temperature (30°C) with reversed phase Phenomenex Luna C8 column (150 mm x 4.6mm i.d.; 4 ?m particle size) and using a mobile phase consisting in water: acetonitrile: tetrahydrofuran (80:15:5 v/v/v) adjusted to pH 2.5, at a flow rate of 1.0 mL/min. Detection was achieved with a UV detector at 357 nm. Method validation investigated parameters such as the sensitivity, linearity (r2= 0.9946), precision, accuracy, recovery and stability. The limit of quantification was 0,25 ?g/mL. Under the assay conditions, doxycycline and oxytetracycline had retention times of 7,5 and 2,4 minutes, respectively. No interferences with endogenous compounds or with anticoagulant were observed. The mean recovery of doxycycline was 84.57%, and 80.73% for the intern standard at working concentration (20?g/mL). The method showed to be precise and accurate both for analyses held in a same day (intra-day) as in different days (inter-days). A good stability of doxycycline and oxytetracycline was observed during extraction and analysis, when stored over a fourmonth period at -20°C, on the auto sample during 24 hours and to 3 freeze-thaw cycles. The present method is suitable for sensitive, precise and accurate determination of doxycycline concentrations in human plasma, within the limits established for this type of analyses